Oestrogen differentially modulates lymphoid and myeloid cells of the European sea bass in vitro by specifically regulating their redox biology. Issue 86 (March 2019) - Paiola, Matthieu; Moreira, Catarina; Duflot, Aurélie; Knigge, Thomas; Monsinjon, Tiphaine
Abstract: Besides their obvious role in sex determination and reproduction, oestrogens display a prominent and complex immunomodulatory role across all vertebrates. To date, our knowledge on the oestrogenic immunomodulation in non-mammalian species is, however, scarce. In both teleosts and mammals, the direct immunomodulatory function of oestrogen is underscored by the presence of multiple oestrogen receptor subtypes in the various immune cells. For a better understanding of the regulatory processes, we investigated the oestrogen receptor expression in two major lymphoid organs of European sea bass: the head-kidney and the spleen. All oestrogen receptor subtypes, including nuclear and membrane oestrogen receptors, were present in both immune organs as well as in the isolated leucocytes. The same findings have been previously made for the thymus. To determine the oestrogen responsiveness of the different immune cell populations and to evaluate the importance of non-genomic and genomic pathways, we assessed the kinetics and the concentration dependent effects of 17β-oestradiol on isolated leucocytes from the head-kidney, the spleen and the thymus in vitro . Given the importance of reactive oxygen species as signalling and defence components in mammalian immune cells, the oxidative burst capacity, the redox status and the viability of both lymphoid and myeloid cells were measured by flow cytometry. The treatment with 17β-oestradiol specifically modulated these parameters depending on (1) the time kinetic, (2) the concentration of 17β-oestradiol, (3) the immune cell population (lymphoid and myeloid cells) as well as (4) the lymphoid organs from which they originated. The observed in vitro oestrogenic effects as well the presence of various oestrogen receptor subtypes in the immune cells of sea bass suggest a complex and direct oestrogenic action via multiple interconnected oestrogen-signalling pathways. Additionally, our study suggests that the oestrogenic regulation of the sea bass immune function involves a direct and tissue specific modulation of the immune cell redox biology comprising redox signalling, NADPH-oxidase activity and H2 O2 -permeability, thus changing oxidative burst capacity and immature T cell fate because oestrogen impacted thymocyte viability. Importantly, immune cells from both primary and secondary lymphoid organs have shown specific in vitro oestrogen-responsiveness. As established in mammals, oestrogen is likely to be specifically and directly involved in immature T cell differentiation and mature immunocompetent cell function in sea bass too. Highlights: Head-kidney and spleen leucocytes of sea bass express oestrogen receptor transcripts. 17β-oestradiol (E2) modulates immune cell redox biology and viability in vitro . E2 has context- and time-dependent action according to the leucocyte population. E2 alters the viability of thymic lymphoid cells only. 2 h of E2-exposure modulated the oxidative burst capacity of head-kidney leucocytes only.